Alternative Solution of Rabbit Development in the Lowlands - Syamsu Bahar (Indonesian Center for Animal Research and Development, 2022)
Rabbits are known as livestock suitable to be raised in highland areas with relatively low temperatures. However, rabbits can still survive in lowland areas with relatively high temperatures. Several aspects should be considered to achieve an efficient and profitable rabbit production. An intensive rearing system should be carried out especially in selecting good breeding stock and providing a good nutritional feed. Environmental condition is important to be aware of since the condition that is less appropriate for rabbits, may cause lower production. The purpose of this paper is to discuss the problem and solution for developing rabbit production in lowland areas. The breed of rabbit and type of feed that is used for lowland areas are discussed. The main obstacle to raising rabbits in lowland areas is the relatively high temperature. Therefore, climate engineering around the cage becomes an important effort to reduce the air temperature, hence, providing a comfortable environment for rabbits to grow and reproduce.